ORGANIZATIONAL CULTURE OF HIGHER EDUCATION INSTITUTIONS AS A FACTOR FOR IMPROVING THE QUALITY OF EDUCATIONAL SERVICES - POPELO, Olha; MELNYCHENKO, Anatolii (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article examines the impact of the organizational culture of higher education institutions on the quality of providing educational services. It has been proven that the organizational culture of a higher education institution should adapt to the modern conditions of the development of the educational environment, take into account social changes and trends, and also be aimed at achieving the goal, fulfilling tasks and developing the higher education institution in accordance with modern educational trends. It is substantiated that for the formation and development of the organizational culture of a higher education institution, there is not time, but the observance of certain principles, which include: purposefulness, unity, systematicity and democracy. A conceptual model of the formation and development of organizational culture of a higher education institution was developed, outlining the stages of formation and development of organizational culture, its functions and factors influencing its development.The article claims that organizational culture as a system of formed shared values, beliefs, and behavior of employees of higher education institutions, which ensures interaction with the external environment and makes it possible to achieve the set goals of the higher education institution's development, affects the improvement of the quality of higher education. It has been proven that the implementation of a model for the formation and development of the organizational culture of a higher education institution in accordance with the principles of purposefulness, unity, systematicity, and democracy makes it possible to create an atmosphere for encouraging teachers, students of higher education, administration to participate in a meaningful dialogue and jointly achieve the set goal and solve the relevant tasks .
Keywords: organizational culture; institution of higher education; university; educational environment; quality of educational services; higher education; students of higher education